Тhе Post-Yield Analysis of Rigid Plastic Beams Columns and Frames - Duszek, M.K.; Łodygowski, T. (Engineering Transactions, 1985)
In: the paper the influence of second-order geometrical effects on the post-yield behaviour of plastic structures is considered. The presentation is limited to the purely mechanical (isothermal) theory and quasi-static deformation processes. The problem considered is illustrated by means of the examples of rigid-plastic beams with various kinds of partial end fixity, the rigid-plastic columns loaded by vertical and horizontal forces and multi-story portal frames. It is demonstrated that plastic deformations may result in changing the boundary conditions in such a way that the stabilizing effect of tensile axial forces is reduced. By making the proper choice of sonie factors unstable mechanisms and catastrophic collapse can be avoided.